INVENTARISASI DAN PEMETAAN POHON BUAH (EDIBLE FRUITS) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) DIKLAT FAHUTAN UNMUL SAMARINDA - Maria Yani Mapa; Rita Diana; Hastaniah Hastaniah; Paulus Matius; Rustam Rustam (Tengkawang : Jurnal Ilmu Kehutanan, 2022)
Forest areas with special purpose of forestry education and training of Forestry Faculty of Mulawarman University, is a tropical rainforest with a variety of vegetation types, including woody trees, lianas, herbs, and many types of edible fruit trees. The objective of this study was to inventory and map the distribution of edible fruit trees, as well as to calculate the diversity index. This study was carried out at KHDTK, Faculty of Forestry, Mulawarman University. It was carried out between December 2021 and July 2022. The technique used in this study directly recorded fruit trees at the research site. Transect sampling was used for the study, with A transect having a width of 20 m and a length of 920 m, 1000 m for transect B, 1000 m for transect C, and 600 m for transect D. The transect line will be determined with the intention of crossing the contour line, taking into account the representativeness of the observed community type. The study's four transects recorded 18 tree species from 235 individuals. This result found 12 edible fruits in transect A, eight edible fruits in transect B, 12 edible fruits in transect C, and seven edible fruits in transect D. This study reveals four dominant Moraceae species: Artocarpus elasticus, Artocarpus rigidus, Artocarpus longifolius, Artocarpus lanceifolius, and Artocarpus integer.Keywords: Inventory, KHDTK, edible fruits AbstrakKawasan hutan hujan tropis yang terdapat di Samarinda sangat tinggi dengan keanekaragaman vegetasi antara lain merantian, semak belukar, liana dan rerumputan, serta aneka tumbuhan buah-buahan yang dapat dimakan. Tujuan dari penelitian ini adalah untuk menginventarisasi dan memetakan sebaran pohon buah-buahan yang dapat dimakan serta menganalisis tingkat keanekaragaman pohon buah tersebut. Penelitian ini dilakukan di HDTK Diklat Kehutanan Fahutan Unmul pada bulan Desember 2021 sampai dengan Juli 2022. Metode yang digunakan adalah dengan pencatatan pohon buah-buahan secara langsung di lokasi penelitian dengan membuat transek. Setiap transek memiliki lebar 20 m dan panjang 920 m untuk transek A, 1000 m untuk B 1000 m, 1000 m untuk C 1000 m dan 600 m untuk D. Hasil keempat transek tersebut mencatat 18 jenis pohon dari total 235 individu. Transek A memiliki 12 spesies, transek B memiliki 8 spesies, transek C memiliki 12 spesies, dan transek D memiliki 7 spesies. Hasil penelitian menunjukkan bahwa jenis pohon buah-buahan yang paling banyak ditemukan adalah dari famili Moraceae, yaitu Artocaprus elasticus, A.rigidus, A. longifolius, A. lanceifolius dan A. integer.Kata Kunci: Inventarisasi, Kawasan Hutan dengan Tujuan Khusus, Pohon penghasil buah